Meningkatkan Hasil Belajar Siswa Materi Masalah Sosial dengan Menerapkan Model Pembelajaran Group Investigation - Hariatun Insiah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The aim of the study was to improve students achievement in learning social problems at the forth grade students of SD Negeri 18 Lubuklinggau by using group investigation model. The study was a classroom action research (CAR). The study was conducted such as pre cycle was on April 15th 2018, cycle I was on April 21st 2018, and cycle II was on April 28th 2018. The result: there were 10 students (43,47%) who pass the passing grade and 13 students (56,53%) who fail. In cycle I, there were 13 students who pass (56,52%) and 10 students who fail (43,48). In cycle, there were 20 students (86,95%) who pass and 3 students (13,05) who fail. In conclusion, the application of group investigation model improved students learning achievement. Keywords: Learning Achievement, Teaching Method, Group Investigation,